EXPLORING GENDER REPRESENTATION: PATRIARCHAL PERPECTIVES FROM EFL SECONDARY SCHOOL TEXTBOOKS IN INDONESIA - Emaliana, Ive; Tusita, Arcci (International Journal of Research -GRANTHAALAYAH, 2019)
This paper seeks to investigate whether the Indonesian government's attempt to promote a gender-equal society in recent decades and improve gender awareness are reflected in patterns of gender representation in EFL textbooks in secondary schools. The study made an analysis of four compulsory textbooks published in 2016 with corpus linguistic tools (e.g. pronouns, occupation, amount of talk) and how gender is represented in the visuals (or illustrations) through conducting frequency counts of the occurrence of male and female characters and the spheres of activities they engaged, to investigate the ration of female-to-male appearances, the extent of use of gender-neutral, and gender-marked constructions, common address titles for reference, and order of appearance of women and men. The findings show that there is a need for evaluation of the existing language textbooks in secondary schools, with the aim of promoting a more gender-balanced learning material. Moreover, the classroom teachers raise the need for the promotion of initial as well as in-service training for teachers on issues of ‘gender stereotypes’, ‘language sexism’ and ‘gender-mainstreaming policies’.